2017
DOI: 10.1111/jmi.12644
|View full text |Cite
|
Sign up to set email alerts
|

FIB‐fabricated complex‐shaped 3D chiral photonic silicon nanostructures

Abstract: SummaryTechnologies capable of fabricating complex shaped silicon metasurfaces attract increasing attention. The focused ion beam fabrication technique is considered traditionally as causing thick damaged layers in silicon resulting in a significant rise of the optical absorption loss. We examine the structure of the FIB-fabricated nanostructures on the silicon-on-sapphire (SOS) platform and its optical characteristics before and after thermal oxidation. We show that being thermally oxidised the FIB-patterned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Although some early works suggested the possibility to restore the functionality of FIB-exposed silicon waveguides by annealing 19 , the particular prospects remained unexplored for a decade. Our recent electron microscopy studies have confirmed that FIB patterning of a SOS film generates a 50 nm thick damaged surface layer, which is also heavily contaminated with implanted gallium atoms 36 . Optical transmission measurements confirmed this layer to have an extremely adverse effect on the optical properties.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Although some early works suggested the possibility to restore the functionality of FIB-exposed silicon waveguides by annealing 19 , the particular prospects remained unexplored for a decade. Our recent electron microscopy studies have confirmed that FIB patterning of a SOS film generates a 50 nm thick damaged surface layer, which is also heavily contaminated with implanted gallium atoms 36 . Optical transmission measurements confirmed this layer to have an extremely adverse effect on the optical properties.…”
Section: Introductionmentioning
confidence: 56%
“…The optical studies of the fabricated metasurface presented below confirm this general rule. Our recent transmission electron microscopy studies 36 have revealed that processing with FIB gives rise to a 50 nm thick layer of damaged silicon, where the crystalline structure is altered and Ga atoms are implanted.…”
Section: Resultsmentioning
confidence: 99%
“…As new nanotechnological approaches are being constantly introduced for the optical metasurface fabrication, the multitude of their designs steadily expands. For example, silicon nanostructures of truly threedimensional chiral shapes have been lately imprinted in monocrystalline silicon using digitally controlled focused ion beam [21]. The technique is capable of producing smooth complex shaped periodic corrugations of the silicon surface, and allowed creating highly transparent metasurfaces with strong optical chirality [22].…”
Section: Introductionmentioning
confidence: 99%
“…Structured complex silicon components have the potential to develop breakthrough applications in solar cells, biomedical engineering, microfluidics, and MEMS for enhancing the functionality and performance of silicon components [1][2][3][4]. Traditionally, chemical-etching and focused ion beam are used to fabricate micro-nano structured silicon surfaces, but their low machining efficiency makes them unsuitable for complex structures with feature sizes in the range of hundreds of micrometres [5][6][7]. Some researchers have tried to machine structured surfaces using ultrashort pulsed lasers owing to the high material removal rate [8][9][10].…”
Section: Introductionmentioning
confidence: 99%